OP78 Picturing ELSI+: Mapping Ethical, Legal, Social And Value Issues. (2019) - Krahn, Murray; Bremner, Karen; de Oliveira, Claire; Almeida, Nisha; Clement, Fiona; Lorenzetti, Diane; O'Campo, Patricia; Pechlivanoglou, Petros; Tricco, Andrea
Abstract : Introduction: Health technology assessment (HTA) is value-laden. Consideration of ethical, legal, and social issues (ELSI), and patient values (ELSI+), is challenged by lack of conceptual clarity and the multi-disciplinary nature of ELSI + . This study used concept mapping to identify key concepts in the ELSI+ domain and their interrelationships. Methods: We conducted a scoping review using Medline and EMBASE (2000-2016, English language) with search terms related to ethics, legal/law, social/society/patient, "ELSI", and HTA/technology/assessment. Items from the review and additional items from an expert brainstorming session were consolidated into 80 ELSI+-related statements which were entered into Concept Systems® Global MAX software. Participants (N = 38; 36 percent researchers, 21 percent academics; 42 percent self-identified as HTA experts) sorted the statements into thematic groups that made sense to them, and rated the statements on their importance in decision-making about adoption of technologies in Canada: 1 (not at all important), 5 (extremely important), 2, 3, and 4 (unlabeled). We used Concept Systems® Global MAX software to create and analyze concept maps with four to 16 clusters, which were reviewed by the study team. Results: We selected the map with five clusters because its clusters represented different concepts and the statements within each cluster represented the same concept. Based on the concepts, we named these clusters: patient preferences and experiences, patient quality of life and function, patient burden/harm, fairness, and organizational. The highest mean importance ratings were for the statements in the patient burden/harm (3.82) and organizational (3.92) clusters. Conclusions: This study suggests an alternative approach to conceptualize the domains originally described as "ELSI+". We identified clusters of relevant concepts that focus on patient perspectives (preferences, experiences, quality of life, function), burden and harm, fairness (individual and societal), and organizational issues. Basing ELSI+ on conceptual consonance, rather than academic disciplines or traditions, provides a framework for coherent consideration of ELSI+ in HTA.